Serum levels of fat-soluble vitamins in children with attention deficit hyperactivity disorder and relationship with symptom subtypes - Li, Mengqi; Gu, Hailin; Chen, Yan (Frontiers in Psychiatry, 2025)
ObjectiveTo evaluate the levels of vitamin A (VA), vitamin D (VD) and vitamin E (VE) in children with Attention deficit hyperactivity disorder(ADHD) and analyze their association with ADHD symptoms.MethodsA total of 657 children aged 4–10 years were collected, of whom 219 were diagnosed with ADHD (including 100 cases of attention deficit major, 14 cases of hyperactive impulsivity major, and 105 cases of mixed type) and 438 were used as healthy controls. High performance liquid chromatography (HPLC) was used to detect serum VA, VD (D2, D3 and total VD) and VE levels. The Weiss Functional Deficit Rating Scale (WFIRS) was used to evaluate the clinical symptoms of ADHD.ResultsThe serum levels of VA, VD (D2, D3, total VD) and VE in the ADHD group were significantly lower than those in the control group. Among the different subtypes, the levels of VD3, total VD and VA in the attention deficit type and mixed type were significantly different from those in the control group, and the levels of total VD and VA in the hyperactive and impulsive type were significantly different. There was a correlation between the total score of ADHD symptoms and the scores of each dimension and vitamin levels.ConclusionThe level of fat-soluble vitamins is significantly correlated with the prevalence, subtype symptoms and functional deficits of ADHD, suggesting that VA, VD and VE supplementation may be the adjuvant treatment for ADHD, but the specific causal relationship needs to be verified by further prospective studies.